2014
DOI: 10.1177/0894318414558616
|View full text |Cite
|
Sign up to set email alerts
|

Linking Native American Tribal Policy to Practice in Mental Health Care

Abstract: The authors highlight approaches used in implementing tribal policy to provide a successful culturally-based modification of dialectical behavior therapy in the Suquamish Native American Tribe. The modified program was called Healthy and Whole. This work fostered greater tribal community resiliency despite the serious mental health problems of the community. It also strengthened tribal policies that support mental health treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Furthermore, the decision to include only published literature biased the review towards considering effective DBT implementations as most trials and programme descriptions reported positive results. In particular the literature reviewed, with the exception of a DBT implementation with Native Americans [43], cannot inform how DBT implementation is achieved with marginalised and particularly high risk populations, such as cultural minority groups. When more information about DBT implementations with such populations become available, the framework may require refinement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the decision to include only published literature biased the review towards considering effective DBT implementations as most trials and programme descriptions reported positive results. In particular the literature reviewed, with the exception of a DBT implementation with Native Americans [43], cannot inform how DBT implementation is achieved with marginalised and particularly high risk populations, such as cultural minority groups. When more information about DBT implementations with such populations become available, the framework may require refinement.…”
Section: Discussionmentioning
confidence: 99%
“…As seen in Table 2, nine papers collected retrospective ( [23][24][25][26][27][28][29][30][31]) and five papers ( [32][33][34][35][36]) collected prospective implementation data. There were 16 programme descriptions ( [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]) and 19 trial process analyses ( [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71]). The majority (N = 38) of papers were from the United States (US), and most implementations of DBT we...…”
Section: Critical Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…During training, teams and team leads should consider who has the necessary skills for the role. Team leads will need to have sufficient skill and organisational connections to effectively liaise with the wider organisation to ensure the team has necessary resources, including funding (Kinsey & Reed, 2015) and to protect the team as far as possible from wider organisational pressures. Ideally, team leads have a more senior position in the wider system combined with influencing skills.…”
Section: A Further Fifth Function Structuring the Environment Becommentioning
confidence: 99%